Evaluation of SICAP pre-employment supports - Adele Whelan; Judith Delaney; Séamus McGuinness; Emer Smyth (The Economic and Social Research Institute (ESRI), 2020)
New ESRI research shows improved employment outcomes among the long-term unemployed who receive employment supports under the Social Inclusion and Community Activation Programme (SICAP).
Keywords: 330; Arbeitslosigkeit; Langzeitarbeitslosigkeit; Coronavirus; Arbeitsmarktintegration; Irland